Censorship: Facebook, Facebook Messenger, Instagram, Signal, Telegram, W (Bangladesh) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in Bangladesh. Data sourced from CensoredPlanet.
Censorship Incident ID: BD-2024-0002. Severity: warning. Confidence: 75%